Chronic Lymphocytic Leukemia and the Kidney. Issue 2 (May 2017) - Sethi, Akash; Rhodes, Joanna; Mato, Anthony; Hogan, Jonathan J.
Chronic lymphocytic leukemia (CLL) is a neoplasm of small mature B lymphocytes, and is the most common leukemia in the Western hemisphere with an estimated 18, 650 cases diagnosed in 2016 and almost 5, 000 deaths. Kidney disease in patients with CLL may impact survival, and occurs through mechanisms such as leukemic infiltration, extra-renal obstruction, tumor lysis syndrome, glomerular disease, and medication side effects. Here, we review kidney disease associated with CLL and its treatments.